2013
DOI: 10.1111/php.12029
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State NMR Spectroscopy to Probe Photoactivation in Canonical Phytochromes

Abstract: The photoreceptor phytochrome switches photochromically between two thermally stable states called Pr and Pfr. Here, we summarize recent solid-state magic-angle spinning (MAS) NMR work on this conversion process and interpret the functional mechanism in terms of a nano-machine. The process is initiated by a double-bond photoisomerization of the open-chain tetrapyrrole chromophore at the methine bridge connecting pyrrole rings C and D. The Pr-state chromophore and its surrounding pocket in canonical cyanobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 113 publications
2
52
0
Order By: Relevance
“…They are biosynthesized as the Pr form in the dark, which can be phototransformed into the biologically active Pfr form upon exposure to R light. The absorption of R light by the Pr form triggers a Z-to-E isomerization of the chromophore and leads to reversible conformational changes throughout the protein moiety, resulting in the Pfr form (Vierstra and Zhang, 2011;Song et al, 2013;. Conversely, the Pfr form can be converted to the Pr form by the absorption of FR light.…”
mentioning
confidence: 99%
“…They are biosynthesized as the Pr form in the dark, which can be phototransformed into the biologically active Pfr form upon exposure to R light. The absorption of R light by the Pr form triggers a Z-to-E isomerization of the chromophore and leads to reversible conformational changes throughout the protein moiety, resulting in the Pfr form (Vierstra and Zhang, 2011;Song et al, 2013;. Conversely, the Pfr form can be converted to the Pr form by the absorption of FR light.…”
mentioning
confidence: 99%
“…In this context it is interesting to refer to recent NMR studies of the prototypical cyanobacterial phytochrome Cph1 (65). These authors have shown a less ordered chromophore pocket in the Pr state, whereas in the Pfr state the chromophore gives rise to well defined resonances with no indication for heterogeneities.…”
mentioning
confidence: 99%
“…In general, red light absorption by the Pr 2 dark state leads to formation of the Pfr state that is photoconverted by far-red light back to Pr, physiological signaling being switched by state transition. The structural characteristics of Pr and Pfr, the photoconversion mechanism, and the physiological signals generated are all subjects of intense research (1)(2)(3).…”
mentioning
confidence: 99%